Sudden gains in internet cognitive therapy for social anxiety disorder in routine clinical practice - See Heng Yim; David M. Clark; Paul M. Salkovskis; Graham R. Thew (Internet Interventions, 2024)
Background: Sudden gains are large symptom improvements between consecutive therapy sessions. They have been shown to occur in randomised controlled trials of internet-delivered psychological interventions, but little is known about their occurrence when such treatments are delivered in routine clinical practice. Objective: This study examined the occurrence of sudden gains in a therapist-guided internet-delivered Cognitive Therapy intervention for social anxiety disorder (iCT-SAD) delivered in the UK NHS talking therapies for anxiety and depression (formerly known as IAPT services). It aimed to assess whether sudden gains were associated with better therapy outcomes, and examine changes in process variables around the period of sudden gains. Methods: The study examined sudden gains based on the Liebowitz Social Anxiety Scale. Of 193 treated patients, 146 provided sufficient data to permit analysis. Linear mixed effects models were used to examine the impact of sudden gains on clinical outcomes, and examine changes in negative social cognitions, self-focused attention, and depressed mood. Results: Seventy sudden gains were found among 57 participants. The occurrence rate of sudden gains was 39 %. Individuals who experienced sudden gains had a larger reduction in social anxiety symptoms at end of intervention and at three-month follow-up. There was evidence of a reduction in the frequency of negative social cognitions prior to the gain, whereas changes in self-focused attention occurred simultaneously with the gain. Depressed mood did not show significant changes over these timepoints. Conclusions: Approximately 2 in 5 patients experienced a sudden gain whilst accessing the iCT-SAD intervention in routine practice. They were associated with better clinical outcomes following treatment compared to those who did not experience a sudden gain.